Quantification of lapidary epigraphy for ancient Sicily - Prag, J (University of Oxford, 2019)
Data is based upon exports from the data held in the EpiDoc TEI-XML files of the I.Sicily project which contains XML editions of the inscribed texts of ancient Sicily. The data was extracted after indexing of the files using an eXist database, piped into csv files through the use of export function of www.ag-grid.com employed on the ISicily website (http://sicily.classics.ox.ac.uk). The datasets are based on the data in I.Sicily as of 22.06.2016. That precise dataset at the time of export is no longer preserved. The current state of the data can be found at http://sicily.classics.ox.ac.uk or at https://github.com/JonPrag/ISicily/ where the commit history enables retrieval of past datastates back to January 2017. Quantitative study of the epigraphic culture of ancient (Greco-Roman) Sicily